1985
DOI: 10.1002/tera.1420320210
|View full text |Cite
|
Sign up to set email alerts
|

Gonadal dysgenesis induced by prenatal exposure to ethinyl estradiol in mice

Abstract: Daily oral administration of ethinyl estradiol (0.02, 0.2, or 2.0 mg/kg of body weight) to pregnant Jc1:ICR mice resulted in ovotestis and intra-abdominal testis with persistent Müllerian duct and Wolffian duct in male fetuses and ovarian hypoplasia in female fetuses when it was given from day 11 through day 17 of gestation (before gonadal differentiation in the fetus). The ovotestis consisted of testicular and ovarian portions. In the testicular portion, a few solid seminiferous tubules containing spermatogon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

1986
1986
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…A mechanism for how oestrogen exposure may affect the meiotic process in female germ cells is indicated in studies of mice which were exposed prenatally to ethinyl oestradiol ovarian germ cell (Yasuda et al, 1977;Yasuda et al, 1985). A reduced number of follicular cells and normal primordial follicles as well as an increased number of degenerating follicles were found in Matched the ovaries of mice whose mothers were treated on days 1 1-OR 95% CL 17 of gestation.…”
Section: Matchedmentioning
confidence: 99%
“…A mechanism for how oestrogen exposure may affect the meiotic process in female germ cells is indicated in studies of mice which were exposed prenatally to ethinyl oestradiol ovarian germ cell (Yasuda et al, 1977;Yasuda et al, 1985). A reduced number of follicular cells and normal primordial follicles as well as an increased number of degenerating follicles were found in Matched the ovaries of mice whose mothers were treated on days 1 1-OR 95% CL 17 of gestation.…”
Section: Matchedmentioning
confidence: 99%
“…Testicular maldescent can be produced experimentally in animals by administering diethylstilbestrol (DES) or other forms of oestrogen during gestation (Jean, 1973;McLachlin et al, 1975;Nomura & Kanzaki, 1977;Yasuda et al, 1985). A number of clinical studies have found an increased frequency of cryptorchidism in males with a history of DES exposure in utero (Cosgrove et al, 1977;Whitehead & Leiter, 1981).…”
mentioning
confidence: 99%
“…34 The same associations have been suggested in humans, 38 although they are still under debate. 39 Sons of women who themselves were exposed in utero to diethylstilbestrol (DES), may have an elevated risk of TC although the data are not unequivocal.…”
Section: The Oestrogen Hypothesismentioning
confidence: 54%
“…Exposure of pregnant mice to oestrogens has been found to increase the frequency of testicular dysgenesis 34 , cryptorchidism 35 , hypospadias 36 and TC 37 in male offspring; and there is also evidence of impaired Leydig cell development and reduced Sertoli cell numbers, resulting in impaired spermatogenesis. 34 The same associations have been suggested in humans, 38 although they are still under debate.…”
Section: The Oestrogen Hypothesismentioning
confidence: 99%